UPAYA KEPALA SEKOLAH MENINGKATKAN MUTU KBM DI MI SYARIF ABBAS TANAH BUMBU - Bulkis, Bulkis; Moh. Luthfi; Moh. Luthfi (UNISAN JURNAL, 2025)
This study aims to describe the efforts of the principal in improving the quality of teaching and learning activities (TLA) at Madrasah Ibtidaiyah (MI) Syarif Abbas, Tanah Bumbu Regency, during the 2024/2025 academic year. The research focuses on: (1) the principal’s planning strategies to enhance the quality of TLA, (2) the implementation of quality improvement programs, and (3) the principal’s evaluation of learning activities. This study employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and documentation involving the principal, teachers, and staff. The results indicate that the principal plays a strategic role in planning quality improvements by setting work programs based on school needs, enhancing teacher competencies, and empowering educational resources. In implementation, the principal conducted academic supervision, professional teacher coaching, classroom management strengthening, and provision of supporting facilities. Evaluation is carried out through regular monitoring, learning reflections, and analysis of student learning outcomes. These efforts positively impact the quality of learning processes, teacher discipline, and student motivation. This study affirms that the effectiveness of school leadership is a key factor in improving the quality of teaching and learning activities in primary Islamic schools.